Antigovernment Networks in Civil Conflicts: How Network Structures Affect Conflictual Behavior. Issue 4 (28th May 2013) - Metternich, Nils W.; Dorff, Cassy; Gallop, Max; Weschle, Simon; Ward, Michael D.
<x xml:space="preserve">Abstract</x> In this article, we combine a game‐theoretic treatment of public goods provision in networks with a statistical network analysis to show that fragmented opposition network structures lead to an increase in conflictual actions. Current literature concentrates on the dyadic relationship between the government and potential challengers. We shift the focus toward exploring how network structures affect the strategic behavior of political actors. We derive and examine testable hypotheses and use latent space analysis to infer actors' positions vis‐à‐vis each other in the network. Network structure is examined and used to test our hypotheses with data on conflicts in Thailand from 2001 to 2010. We show the influential role of network structure in generating conflictual behavior.